Pengaruh Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Beras SPHP Melalui Minat Beli Konsumen Perum Bulog di Kota Tanjungpinang - Isnovera Asdayanti; Iranita Iranita; Lastri Anggi Fani (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of product quality and brand image on the purchasing decisions of SPHP rice at Perum BULOG in Tanjungpinang City through purchase intention as an intervening variable. This study employed a quantitative approach. The population of this study consisted of SPHP rice consumers in Tanjungpinang City. The sampling technique used was purposive sampling, with a total sample of 110 respondents. Data were collected through questionnaires and analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with the assistance of SmartPLS 4.0 software. The results indicate that product quality has no significant effect on purchasing decisions. However, product quality has a positive and significant effect on purchase intention. Brand image has a positive and significant effect on both purchasing decisions and purchase intention. In addition, purchase intention has a positive and significant effect on purchasing decisions. The mediation test results reveal that purchase intention is unable to mediate the effect of product quality on purchasing decisions, but it successfully mediates the effect of brand image on purchasing decisions of SPHP rice at Perum BULOG in Tanjungpinang City. The findings of this study indicate that brand image and purchase intention are important factors in encouraging consumers' purchasing decisions for SPHP rice.